Alexandr Sergeyevich Lisetskiy and his collection of bats in the Museum of Nature at V.N.Karazin Kharkiv National University - Ilyukhin, Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Aleksandr Sergeyevich Lysetskiy (1919–1991), whose centenary is celebrated this year, was a well-known ornithologist and mammologist and worked for a long time as an associate professor at the Department of Zoology at Kharkiv University. He has been interested in zoology since childhood and has been a young naturalist at the Kharkov Pioneer Palace and in Kharkiv Zoo as early as 1934. A.Lysetskiy started his studies at the biological faculty of KhNU in 1938 and finished it after the Great Patriotic War in 1948. Already in these years (from 1937 to 1947) he, together with his student friend A.Kunichenko, collected bat specimens, which are now stored in the Museum of Nature of KhNU. Since the labels of almost all specimens do not have the names of collectors, this collection was determined by us by comparing all the data (collection numbers, dates etc.) of the samples with the data given in their paper "To the bat fauna (Chiroptera) of Kharkiv region», which was published in 1952. In total, the Museum of Nature collection now has 139 specimens of bats from 18 species, 11 genera and 3 families. The majority – 129 specimens belong to the family Vespertilionidae. Of these, 52 specimens were collected by A.Lisetskiy (together with A.Kunichenko). This material is provided in the comparative table. Of the 9 species of this family represented in their collection, 6 species are representing fifty or more percent of the total number of all specimens stored in the Museum of Nature. These species are: Myotis dasycneme (66.6%), Plecotus auritus (75%), Nyctalus lasiopterus (100%), Nyctalus leisleri (55%), Pipistrellus nathusii (83.3%), Vespertilio murinus (100%). Only these collectors provided specimens of two species: these are the only specimen of Nyctalus lasiopterus and both specimens of Vespertilio murinus. Nowadays, all of these specimens (except Nyctalus lasiopterus, which is on display) are stored in separate boxes in the scientific collection of the museum. We can conclude that the collection of A.Lisetskiy and A.Kunichenko make up the prevailing part of the scientific collection of bats of the Museum of Nature of Kharkiv University.